Legal Compliance In Health Care Services: A Systematic Review - Hilmy, Mohamad Reza; Putranto, Rahmat Dwi; Mahadewi, Erlina Puspitaloka; Setiawan, Ichwan; Shameela, Alika (Dinasti International Journal of Education Management and Social Science, 2026)
This study is driven by the growing demands for legal and regulatory compliance in medical facilities, which are generally seen as extra work for healthcare managers. Simultaneously, management efficiency has emerged as an essential requisite due to resource limitations and increasing service complexity. This study seeks to investigate the link between legal compliance and managerial effectiveness in health services via a methodical literature review methodology. The review adheres to PRISMA principles and examines peer-reviewed journal papers published from 2020 to 2025. Twenty-five carefully chosen studies were organized into themes synthesized to find the main ways that following the law is linked to better management. The results show that legal compliance indirectly improves management efficiency by making governance frameworks stronger, getting accreditation and standardization, managing risks and keeping patients safe, protecting data and information, as well as making managers more committed and changing the culture of the organization. The findings indicate that complying with regulations does not inherently improve efficiency; instead, efficiency improvements occur when compliance is effectively integrated into healthcare management processes. These results show how important it is to think of legal conformity as a strategic supervisory resource that helps provide health services in a way that is both efficient and long-lasting.